Numerical analysis and wave tank validation on the optimal design of a two-body wave energy converter. (January 2020) - Martin, Dillon; Li, Xiaofan; Chen, Chien-An; Thiagarajan, Krish; Ngo, Khai; Parker, Robert; Zuo, Lei
Abstract: To improve the performance of a 'point absorber' type wave energy converter (WEC), an additional submerged body can be deployed. The submerged body can be used to increase the equivalent excitation force on the WEC, as well as provide resonance tuning. This paper presents numerical analysis and experimental validation of a two-body point absorber type WEC using a mechanical motion rectifier (MMR) based power takeoff. The two-body point absorber consists of a floating buoy connected to a neutrally buoyant submerged body via the power-takeoff. The mechanical motion rectifier and a ball screw translate the relative heave motion of the two bodies into unidirectional rotation, which in turn spins a generator. Frequency domain analysis suggests there is an optimal submerged body mass for maximum WEC power absorption. Regular wave simulations in the time domain are compared to the results obtained in the frequency domain. While the time domain and frequency domain results predict the same optimal mass ratio, time domain analysis provides a more complex and accurate power result. To validate the time domain model, experimental wave tank testing is conducted using a 1:30 scale model WEC. The experiment shows the two-body WEC can produce twice the amount of power as the single-body WEC with same floating buoy and can be further increased by PTO design and power electronics optimization. Wave tank testing also shows the two-body WEC has a capture width ratio up to 58% at 59 kW/m and 51% at 36 kW/m. Highlights: Submerged body analysis of a two-body wave energy converter. Wave tank tested on single-body and two-body wave energy converter. Two-body converter produces twice the power of the single-body converter. Capture width ratios are up to 58% at 59 kW/m and 51% at 36 kW/m.